2011
DOI: 10.1002/cm.20504
|View full text |Cite
|
Sign up to set email alerts
|

A cell‐based screen for inhibitors of flagella‐driven motility in Chlamydomonas reveals a novel modulator of ciliary length and retrograde actin flow

Abstract: Cilia are motile and sensory organelles with critical roles in physiology. Ciliary defects can cause numerous human disease symptoms including polycystic kidneys, hydrocephalus, and retinal degeneration. Despite the importance of these organelles, their assembly and function is not fully understood. The unicellular green alga Chlamydomonas reinhardtii has many advantages as a model system for studies of ciliary assembly and function. Here we describe our initial efforts to build a chemical-biology toolkit to a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
27
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 26 publications
(28 citation statements)
references
References 73 publications
(85 reference statements)
1
27
0
Order By: Relevance
“…The library's current format of arrayed colonies on solid medium is compatible with high-throughput robotic screens using colony size as a powerful and versatile phenotype, as illustrated in yeast (Costanzo et al, 2010). The library is also compatible with a range of other quantitative phenotyping methods, including measurement of pigment levels, chlorophyll fluorescence analysis of arrays on agar (Johnson et al, 2009), and motility screens in 96-well plates (Engel et al, 2011).…”
Section: The Mutant Library Opens the Door To Novel Biologymentioning
confidence: 99%
“…The library's current format of arrayed colonies on solid medium is compatible with high-throughput robotic screens using colony size as a powerful and versatile phenotype, as illustrated in yeast (Costanzo et al, 2010). The library is also compatible with a range of other quantitative phenotyping methods, including measurement of pigment levels, chlorophyll fluorescence analysis of arrays on agar (Johnson et al, 2009), and motility screens in 96-well plates (Engel et al, 2011).…”
Section: The Mutant Library Opens the Door To Novel Biologymentioning
confidence: 99%
“…The most plausible explanation is provided by the balance point model, in which cilium length is determined by a balance between cilium assembly and disassembly rates [8], [9]. The assembly rate is dependent on the availability of axonemal tubulin and other structural components, supplemented by anterograde IFT and probably the pool of these proteins at the base of the cilium [10], [11]. Indeed, changes in both anterograde and retrograde IFT are accompanied by changes in cilium length [8], [12][15].…”
Section: Introductionmentioning
confidence: 99%
“…Application of genetic, chemical or even genome-wide small interfering RNA libraries to ciliated cells followed by assessment of signaling or ciliary structure provides an important complementary approach to understanding ciliary-specific genetic requirements [41-44]. These cellular analyses have uncovered many important signaling mechanisms, some of which are pharmacologically tractable and may serve as a basis for the development of future therapy, in particular because the assays can be targeted to bypass specific patient-related cellular defects.…”
Section: Advanced High-throughput Strategies In the Study Of Ciliopatmentioning
confidence: 99%
“…For instance, we found that positive regulators of actin polymerization functioned as negative regulators of ciliogenesis [44], and vice versa, prompting us to question whether actin destabilizers might promote ciliogenesis in cellular models of disease. We found that low dose application of the actin polymerization inhibitor cytochalasin D partially rescued cilum elongation defects caused by the hypomorphic mouse mutation Ift88 [41-44]. Further genomic screening focusing on a specific cellular process, such as ciliation linked to cell cycle regulation, post-translational modification of microtubules and regulation of ciliary transport and signaling, will lead to a greater understanding of ciliary structure/function relationships, their relevance to disease and potential treatments.…”
Section: Advanced High-throughput Strategies In the Study Of Ciliopatmentioning
confidence: 99%